2009
DOI: 10.1007/dcr.0b013e3181a80e24
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Anorectal Morphologic and Functional Parameters After Fistula-in-Ano Surgery

Abstract: Anal continence is significantly affected after fistula-in-ano surgery, mainly because of sphincteric lesions that affect anal canal pressures and that can be imaged with endoanal ultrasound. It is important to preoperatively recognize sphincter defects to allow adequate surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 35 publications
4
33
0
12
Order By: Relevance
“…22,25,26 Cavanaugh et al 22 reported incontinence disorders in 64.0% of the subjects and 59.0% had transsphincteric fistula (both sexes). Garcia-Aguilar et al 25 reported that a higher EAS transaction (50%-70% muscle involvement) resulted in an incontinence rate of 55.0%.…”
Section: Discussionmentioning
confidence: 99%
“…22,25,26 Cavanaugh et al 22 reported incontinence disorders in 64.0% of the subjects and 59.0% had transsphincteric fistula (both sexes). Garcia-Aguilar et al 25 reported that a higher EAS transaction (50%-70% muscle involvement) resulted in an incontinence rate of 55.0%.…”
Section: Discussionmentioning
confidence: 99%
“…So liegt die Häufigkeit der intersphinktären Fistel zwischen 24 und 54 %, der transsphinktären zwischen 30 und 58 % sowie der suprasphinktären zwischen 1 und 20 %. Die Häufigkeit der extrasphinktären Fisteln wird mit bis zu 5 % in älteren Publikationen [313] und bis zu 3 % in neueren Publikationen [349] angegeben. Zu berücksichtigen ist jedoch die Tatsache, dass alle Zahlen aus dem Krankengut koloproktologischer Spezialabteilungen stammen, denen insbesondere komplexe Fisteln (Typ II, III, IV, rektovaginal) zugewiesen werden, so dass hier eine Verschiebung der Zahlen zugunsten dieser Typen anzunehmen ist, wie es das von Malouf et al aufgearbeitete Patientengut des St. Mark's Hospital impliziert [249].…”
Section: Epidemiologieunclassified
“…So liegt die Häufigkeit der intersphinkteren Fistel zwischen 24 und 54%, der transsphinkteren zwischen 30 und 58% sowie der suprasphinkteren zwischen 1 und 20%. Die Häufigkeit der extrasphinkteren Fisteln wird mit bis zu 5% in älteren Publikationen [205] und bis zu 3% in neueren Publikationen [224] angegeben. Zu berücksichtigen ist jedoch die Tatsache, dass alle Zahlen aus dem Krankengut koloproktologischer Spezialabteilungen stammen, denen insbesondere komplexe Fisteln (Typ II, III, IV, rektovaginal) [166].…”
Section: Klassifikationunclassified
“…Ergebnisse nach Rektumvollwandplastik wurden demzufolge in 17 Studien untersucht ( [8,18,48,107,108,133,137,147,177,194,195,196,198,220,224,278,284]; . Tab.…”
Section: Rektumvollwand-flapunclassified